Effect of the reduction of the crude protein content of diets supplemented with essential amino acids on the performance of piglets weighing 6-15kg (2014)
Two experiments were conducted to assess the effect of the reduction of the crude protein (CP) content of diets supplemented with amino acids on piglets weighing 6-15. kg. In the performance experiment (Experiment I), 120 piglets weaned at 21 days of age with initial live weights of 5.95±0.33. kg were distributed into five treatment groups. This grouping followed a randomized block design with eight repetitions and three animals per experimental unit. The treatments consisted of five different diets, in which the CP content were reduced from 21.0% to 15.0% (21.0%, 19.5%, 18.0%, 16.5%, and 15.0% CP); the amino acid requirements of the diet were met by adding L-lysine, DL-methionine, L-threonine, L-tryptophan, L-valine, and L-isoleucine. No differences were found in the variables associated with performance among animals from different treatment groups. Therefore, any of the investigated CP levels can effectively be used in piglet diets supplemented with synthetic amino acids. The essential/nonessential amino acid ratio (EAA:NEAA) increased with the reduction of the CP content, and the best ratio (53:47) was achieved with the diet containing 15% protein. Urea concentrations decreased linearly with protein reduction (Experiment I). To assess the nitrogen balance (Experiment II), 20 crossbred male castrated piglets from a commercial lineage, weaned at 21 days of age, were randomly assigned in two blocks, in which each block had two replicates (four replicates per treatment). The average live weight of the piglets was 10.79±2.19. kg. The animals were housed in metal cages and were distributed into five treatment groups following a randomized block design with four repetitions; the experimental unit consisted of one piglet. The nitrogen excretion and blood and urine urea concentrations decreased linearly (. P < 0.05) with the reduction of CP in the diets, resulting in reduced nitrogen excretion into the environment. © 2014 Elsevier B.V.